Moderasi Beragama Sebagai Hidden Kurikulum di STIT Darul Fattah Bandar Lampung: Moderasi Beragama Sebagai Hidden Kurikulum di STIT Darul Fattah Bandar Lampung - muna waroh (ISLAM EDU : Jurnal Ilmiah Pendidikan Agama Islam, 2023)
Radicalism often occurs in this country, which was previously only directed at less educated groups of people, has now spread to educated groups or students at universities. One of the causes of the emergence of radicalism is due to the fading of Pancasila values ​​with the growth of fanatical attitudes towards certain groups and groups, the emergence of various kinds of organizations that prioritize certain groups and groups, even in the name of Islamic teachings. The Islamic religion originally taught noble values ​​such as; love of peace, compassion, mutual respect for one another, but sometimes religion is interpreted according to the wishes of certain groups as a basis for carrying out their mission through a religious approach using violence and coercion. One thing that can be used to prevent radicalism is understanding religious moderation as an ideology that all students must have. An understanding of religious moderation is used as a hidden curriculum to help students prevent radical traits. This research aims to prevent radicalism at STIT Darul Fattah. The method used in this research is descriptive qualitative methods. The results of this research show that instilling the ideology of religious moderation through the hidden curriculum is very helpful in preventing radicalism at STIT Darul Fattah, so that all students can have an attitude that loves peace, compassion and mutual respect.